Social innovation in cultivation of family medicinal plants at Makrifah Herbal, East Borneo - Abdul Kahar; Muhammad Busyairi; Dian Nurcahya; Yusuf Zihni (Universitas Muhammadiyah Magelang, 2022)
This community sservice aims to strive Makrifah Herbal's long-term viability and prepare the legality of business licensing. In order to decide whether or not to implement an innovation, as well as to ensure its long-term viability, social innovation is required. This program is the implementation of PT Pupuk Kaltim's Corporate Social Responsibility (CSR) program through the cultivation of family medicinal plants in the Makrifah Herbal group. Composting training; marketing training through the marketplace and social media; production and business activity training; business and product licensing assistance; product collaboration; and marketing assistance are some of the methods for implementing community service program. This program focuses on improving the long-term viability of the company. Because it already has a halal certificate from the East Kalimantan MUI and a product distribution permit from the BPOM, CV Makrifah Herbal has met the requirements as a business entity that is ready to compete in the national or global market for herbal products.